Semiotics : the basics - Chandler, Daniel, 1952- (The basics, 2022)
"This fourth edition of the bestselling textbook, now available in print, eBook and audiobook, has been fully updated, continuing to provide a concise introduction to the key concepts of semiotics in accessible and jargon-free language. Demystifying what is a complex, highly interdisciplinary field, key questions covered include: What are signs and codes? What can semiotics teach us about representation and reality? What tools does it offer for analysing texts and cultural practices? The fourth edition of Semiotics: The Basics focuses in particular on its application to communication and cultural studies. It has been extensively revised and extended, with an entirely new section on cognitive semiotics, many more illustrations, and a new glossary. With updates to theory, further examples and suggestions for review and further reading, this must-have resource is both the ideal introductory text and an essential reference guide for students at all levels of language and communication, media and cultural studies"- Resumé vydavatel